2021
DOI: 10.1038/s41598-021-84829-y
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based diagnostics of the auditory system using cochlear implant electrodes as sensors

Abstract: The cochlear implant is one of the most successful medical prostheses, allowing deaf and severely hearing-impaired persons to hear again by electrically stimulating the auditory nerve. A trained audiologist adjusts the stimulation settings for good speech understanding, known as “fitting” the implant. This process is based on subjective feedback from the user, making it time-consuming and challenging, especially in paediatric or communication-impaired populations. Furthermore, fittings only happen during infre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…They were also able to record CAEPs using only CI electrodes, even though the morphology was less clear and peaks were not detectable in all subjects. The CAEPs recorded in the present study show very similar morphologies to the CAEPs presented in the studies of McLaughlin et al (2012) and Somers et al (2021). However, the present experimental setup was not restricted by extensive measurement time and it was based on a clinical transcutaneous implant without requiring an additional external amplifier.…”
Section: Cortical Auditory Evoked Potentials (Caeps)supporting
confidence: 75%
See 4 more Smart Citations
“…They were also able to record CAEPs using only CI electrodes, even though the morphology was less clear and peaks were not detectable in all subjects. The CAEPs recorded in the present study show very similar morphologies to the CAEPs presented in the studies of McLaughlin et al (2012) and Somers et al (2021). However, the present experimental setup was not restricted by extensive measurement time and it was based on a clinical transcutaneous implant without requiring an additional external amplifier.…”
Section: Cortical Auditory Evoked Potentials (Caeps)supporting
confidence: 75%
“…The disadvantage of the approach of McLaughlin et al (2012) was that they required the concatenation of the time-shifted windows causing extensive measurement time to record CAEPs. Somers et al (2021) performed continuous EEG recording via a CI from the company Cochlear Ltd. using a percutaneous connector and a high-quality external amplifier. They tested different electrode configurations and found that the best configuration was a hybrid recording in which the Cz scalp electrode was referenced to an intracochlear electrode.…”
Section: Cortical Auditory Evoked Potentials (Caeps)mentioning
confidence: 99%
See 3 more Smart Citations